Hubungan Kelompok Sebaya dengan Perilaku Bullying pada Siswa Sekolah Dasar - Adrianus Aprilyanto Mone Mone; Ika Arum Dewi Satiti; Jiarti Kusbandiyah (STIKES Widyagama Husada, 2026)
Abstrack Background: School-age children are easy targets for bullying because they begin to leave the family environment and interact and make friends with other children. Bullying occurs when a more powerful person or group intentionally causes harm to another person by doing unwanted things, and this happens repeatedly. Objective: Find out how being part of a peer group affects bullying behavior in elementary school children. Method: This study employed purposive sampling, a method of selecting participants based on specific criteria, and a cross-sectional design, where data was collected at a single point in time. A questionnaire was used to gather information, and the data were analyzed using SPSS software. The Spearman Rank correlation test was used to examine the relationship between variables. Results: Research at SDN 1 Landungsari, Malang City found that there was no strong relationship between the role of peer groups and bullying behavior, with a correlation coefficient value of 0.060 and a significance level of 0.754 (p > 0.05), meaning that although statistically there was a tendency for a very weak positive relationship, the relationship was not strong enough to be inferred as a significant influence. Conclusion: There is no strong relationship between peer influence and bullying behavior. The correlation coefficient is 0.060, and the significance level is 0.754 (p > 0.05). References : 30 references (2011-2025). Keywords : The Role of Peer Groups, Bullying Behavior, School-Aged Childre